OPTIMALISASI PROSES DENGAN METODE COMMONIZE BOOTH B UNTUK MATERIAL X** TWO TONE KANSAI PAINT di LINE TOPCOAT PT ASTRA DAIHATSU MOTOR - Purwoko, Yohanes Agung; Mukhtariz, Akmal; Edi Widyartono, Andreas; Amri, Mahardhika; Febriyanto, Rusdi (Technologic, 2024)
Abstract – PT. Astra Daihatsu Motor Karawang Assembly Plant is a manufacturing company in Indonesia that produces four-wheeled vehicle models for the Daihatsu and Toyota brands. The Painting process is one of the processes in a series of car manufacturing processes at PT. Astra Daihatsu Motor Karawang Assembly Plant. After collecting data related to the achievement of the KPI (Key Performance Index) of the Painting Department, several aspect points were obtained that had not reached the target, one of which was a process aspect point related to efficiency. After being broken down, the Tocpoat Line becomes the main process with the lowest efficiency, which only reaches 87%. With the current achievement of efficiency, in one hour Topcoat is only able to produce 62.6 units/hour from the target of 68.7 units that must be produced. However, with the ability of the current topcoat, it causes a loss of 5.1 units/hour and must be done overtime at the end of production. Therefore, a deeper study was carried out using the QCC 8 Step method which focused on the Topocoat production line, as well as making improvements to one of the efficiency problems, namely Heijunka X** Twotone with the target of increasing efficiency, meeting supply unit needs towards touch ups, and reducing unit loss per hour on the Topcoat production line. After this analysis and improvement was carried out, it was seen that the results of changes in efficiency increase were achieved, which reduced unit loss in the topcoat and were able to save costs related to overtime.Keywords : Pinting Departement KPI, Efficiency Topcoat, Target Unit, Overtime.